Predizendo a distribuição de espécies zooplanctônicas : uma abordagem baseada em modelos de nicho ecológico. - Mantovano, Tatiane (2020)
Predicting the area of species distribution on a regional or global scale is one of the elementary objectives in Macroecology. Ecological niche modeling is a potentially important tool for understanding species distribution patterns based on niche theory as a conceptual basis. Based on the occurrences of species and environmental conditions (bioclimatic data), ecological niche models (ENMs) are correlative models that employ different statistical and mathematical methods seeking to predict potential areas of native and exotic species. Since zooplanktonic organisms can respond quickly to small environmental changes, this study aimed to predict, through ecological niche modeling, the potential distribution of native and exotic zooplanktonic species in the current scenario and on the effects of climate change on this thesis was structured in three independent studies. The first chapter aimed to identify potential or environmentally appropriate areas for the occurrence of Kellicottia bostoniensis in native and non-native regions, using bioclimatic models. In the second chapter, we sought to predict the impacts of climate change on the invasive potential of Daphnia lumholtzi, identifying the susceptibility of hydrographic basins to receive the species, considering the effects of climate and reservoirs as potential agents of invasion. Finally, the third chapter aimed to investigate whether there will be changes in alpha diversity (species richness) in the face of future periods of climate change (2050 and 2080) and to identify the main regions of climate refuge for the occurrence of copepod species. Despite the uncertainties embedded in the species distribution models, the results found in this study can be essential in anticipating the responses of native or exotic species, in the face of the impacts of climate change and, in this sense, serve as subsidies for decision-making bodies that value the conservation of biodiversity, maintenance of ecosystem processes and services.